The shadow land [compact disc, unabridged] : a novel - Kostova, Elizabeth (Books on Tape ; Random House Audio, 2017)
"From the #1 bestselling author of The Historian comes an engrossing novel that spans the past and the present--and unearths the dark secrets of Bulgaria, a beautiful and haunted country. A young American woman, Alexandra Boyd, has traveled to Sofia, Bulgaria, hoping that life abroad will salve the wounds left by the loss of her beloved brother. Soon after arriving in this elegant East European city, however, she helps an elderly couple into a taxi--and realizes too late that she has accidentally kept one of their bags. Inside she finds an ornately carved wooden box engraved with a name: Stoyan Lazarov. Raising the hinged lid, she discovers that she is holding an urn filled with human ashes. As Alexandra sets out to locate the family and return this precious item, she will first have to uncover the secrets of a talented musician who was shattered by oppression--and she will find out all too quickly that this knowledge is fraught with its own danger. Kostova's new novel is a tale of immense scope that delves into the horrors of a century and traverses the culture and landscape of this mysterious country. Suspenseful and beautifully written, it explores the power of stories, the pull of the past, and the hope and meaning that can sometimes be found in the aftermath of loss. --